Energy Subsidy Reform : Lessons and Implications. (Policy Papers; Policy Paper ;, 2013)
Energy subsidies have wide-ranging economic consequences. While aimed at protecting consumers, subsidies aggravate fiscal imbalances, crowd-out priority public spending, and depress private investment, including in the energy sector. Subsidies also distort resource allocation by encouraging excessive energy consumption, artificially promoting capital-intensive industries, reducing incentives for investment in renewable energy, and accelerating the depletion of natural resources. Most subsidy benefits are captured by higher-income households, reinforcing inequality. Even future generations are affected through the damaging effects of increased energy consumption on global warming. This paper provides: (i) the most comprehensive estimates of energy subsidies currently available for 176 countries; and (ii) an analysis of ?how to do energy subsidy reform, drawing on insights from 22 country case studies undertaken by IMF staff and analyses carried out by other institutions.